Does the use of paclitaxel or rapamycin-eluting stent decrease further need for coronary-artery bypass grafting when compared with bare-metal stent? - Lemos Junior, Hernani Pinto de [UNIFESP] (2007)
CONTEXT AND OBJECTIVE: The safety and efficacy of drug-eluting stents reduce the need for surgical revascularization. The objective of the present study was to investigate whether paclitaxel or rapamycin-eluting stent are effective in avoiding the need for coronary-artery bypass grafting.METHODS: This was a systematic review of the literature using the methodology of the Cochrane Collaboration. The type of study considered was controlled randomized trials; the type of intervention was drug-eluting or bare-metal stents; and the main outcome investigated was coronary-artery bypass grafting.RESULTS: The ten studies included in this systematic review did not show any statistically significant difference between the drug-eluting stents and the bare-metal stents with regard to the outcome of coronary-artery bypass grafting (confidence interval: 0.31 to 1.42).CONCLUSION: The surgical revascularization rate was not reduced by the use of drug-eluting stents.